2010
DOI: 10.1007/s00253-010-2517-3
|View full text |Cite
|
Sign up to set email alerts
|

Catalase overexpression reduces the germination time and increases the pathogenicity of the fungus Metarhizium anisopliae

Abstract: Catalases and peroxidases are the most important enzymes that degrade hydrogen peroxide into water and oxygen. These enzymes and superoxide dismutase are the first lines of cell defense against reactive oxygen species. Metarhizium anisopliae displays an increase in catalase-peroxidase activity during germination and growth. To determine the importance of catalase during the invasion process of M. anisopliae, we isolated the cat1 gene. cat1 cDNA expression in Escherichia coli and the subsequent purification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Previous reports established a close relation between the infectivity of entomopathogenic fungi and antioxidant enzymes. Morales‐Hernández et al found that overexpression of the catalase gene cat1 improved the infectivity of M. anisopliae , in addition to faster germination and higher tolerance to hydrogen peroxide. Recently, Wang et al determined the role of five catalase genes in B. bassiana ; the infectivity diminished after the knock‐out of genes catA , catP or catD ; also, these enzymes were linked to thermal tolerance and resistant to UV‐B radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports established a close relation between the infectivity of entomopathogenic fungi and antioxidant enzymes. Morales‐Hernández et al found that overexpression of the catalase gene cat1 improved the infectivity of M. anisopliae , in addition to faster germination and higher tolerance to hydrogen peroxide. Recently, Wang et al determined the role of five catalase genes in B. bassiana ; the infectivity diminished after the knock‐out of genes catA , catP or catD ; also, these enzymes were linked to thermal tolerance and resistant to UV‐B radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of an organism to sublethal stress increases the capacity for resistance not only to that particular type of stress but also to other stresses of a different nature (cross‐protection) . In this context, some reports have determined the role of antioxidant enzymes, mainly superoxide dismutases and catalases, in fungi during hyperoxidant states, and also as a response to different types of stress, which in turn is associated with improved infectivity …”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also observed by Morales Hernandez et al . who observed that over expression of cat1 could be responsible for the germination of M. anisopliae mutant 13–19% faster than the wild type. The transgenic strains overexpressing the cat1 gene had twice the catalase activity of the wild‐type strain, in accord with the extra copy of the gene which is detected in both transgenic samples tested.…”
Section: Discussionmentioning
confidence: 99%
“…In this phase the fungus needs specific proteases able to digest the protein matrix in the host cuticle. Catalase, a detoxifying enzyme able to degrade hydrogen peroxide, plays an important role both in stress tolerance (protection against host oxidative defenses) and growth of entomopathogenic fungi (Morales Hernandez et al, 2010).…”
Section: Differential Gene Expression In Two Infection Stagesmentioning
confidence: 99%